Partisipasi Masyarakat Terhadap Pengelolaan Eduwisata Kampung Susu Dinasty di Desa Sidem Kecamatan Gondang Kabupaten Tulungagung - Eka Putri, Anita; Kurniawati, Elya; Prasad, Ravinesh Rohit; Purwaningtyas, Fauziyah Dwi (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
Abstract: Edutourism is not just presenting an entertainment but must be inserted of educational values ​​for visitors. Edutourism aims to improve the intelligence and creativity of visitors. Kampung Susu Dinasty is one of the new developed educational attractions in the area of ​​Sidem Village, Gondang Sub-District, Tulungagung District. The tourism object emphasizes the education aspect in the field of animal husbandry, especially cattle, goats and horses. The tourist attraction of the Kampung Susu Dinasty has an influence to people's lives, the which one is increasing livelihoods which has an impact on increasing income. To find out the form of community participation in the development of edutourism objects, the Kampung Susu Dinasty is needed for a study. Initial identification is done by field survey. Furthermore, data collection is done by observation, interviews, and questionnaires. Then the data were be analyzed to descriptively qualitatively. This was done to find out the form of community participation in the development of the Kampung Susu Dinasty Farm. The results of the study show geographically that Gondang Subdistrict is a suitable area to be developed for chicken farms, not cattle, goats, or horses. The form of community participation in the development of edutourism in the Kampung Susu Dinasty Ranch is participation in management. In addition, the community has a role in developing the tourist attraction. This is indicated by the existence of changes in livelihoods from the former who worked as brick craftsmen to become tourist managers, souvenir artisans, and open parking lots. The development of edutourism in the Kampung Susu Dinasty Livestock is supported by a public attitude that is open to tourism development.